2020
DOI: 10.1101/2020.07.27.20162362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure to a COVID-19 carrier: transmission trends in respiratory tract and estimation of infectious dose

Abstract: How human respiratory physiology and inhaled airflow therein proceed to impact transmission of SARS-CoV-2, leading to the initial infection, is an open question. An answer can help determine the susceptibility of an individual on exposure to a COVID-2019 carrier and can also quantify the still-unknown infectious dose for the disease. Combining computational fluid mechanics-based tracking of respiratory transport in anatomic domains with sputum assessment data from hospitalized COVID-19 patients and earlier mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
(92 reference statements)
1
22
0
Order By: Relevance
“…Specifically, the minimum infectious dose was estimated by Evans (2020) and Barr (2020) to be~1000, while Ryan et al (2020) estimated a minimum number of 500 infectious particles to be sufficient to activate infection. A value of 300 is suggested by Basu (2020), while a value of 100 was conjectured by Karimzadeh et al (2020). Pfefferle et al (2020) and Basu (2020) hypothesized that even a single viral particle can be sufficient to initiate SARS-CoV-2 infection.…”
Section: Assessment Of the Potential Role Of Airborne Transmissionmentioning
confidence: 91%
See 2 more Smart Citations
“…Specifically, the minimum infectious dose was estimated by Evans (2020) and Barr (2020) to be~1000, while Ryan et al (2020) estimated a minimum number of 500 infectious particles to be sufficient to activate infection. A value of 300 is suggested by Basu (2020), while a value of 100 was conjectured by Karimzadeh et al (2020). Pfefferle et al (2020) and Basu (2020) hypothesized that even a single viral particle can be sufficient to initiate SARS-CoV-2 infection.…”
Section: Assessment Of the Potential Role Of Airborne Transmissionmentioning
confidence: 91%
“…A value of 300 is suggested by Basu (2020), while a value of 100 was conjectured by Karimzadeh et al (2020). Pfefferle et al (2020) and Basu (2020) hypothesized that even a single viral particle can be sufficient to initiate SARS-CoV-2 infection. Other respiratory viruses were found to be characterized by higher or lower infectivity levels.…”
Section: Assessment Of the Potential Role Of Airborne Transmissionmentioning
confidence: 91%
See 1 more Smart Citation
“…The only human study on a coronavirus we found was on HCoV-229E with the TCID50 comparison was 13 (6). The infective dose in humans for COVID-19 was estimated as n×100 particles based on computational analysis of nasopharynx in transmission and inhalation of droplets (80). In animals the minimum dose of SARS-CoV-2 that infected immunocompromised hamsters were also 100 particles (35), whereas healthy ferrets and transgenic mice were infected at slightly higher dose of 500 particle by nasal (16) and 630 particles by aerosol route (20).…”
Section: Discussionmentioning
confidence: 99%
“…This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as: Seyer A, The transmission of SARS-CoV-2 can occur via aerosols or contaminated fomites (1), and the COVID-19 infective dose is estimated to be approximately 300 (6). Besides respiratory tract secretions, the SARS-CoV-2 genome was also detected in saliva, urine, and stool samples, stating other possible transmission ways, such as faecal-oral or faecal-respiratory transmission (7).…”
mentioning
confidence: 99%